Nd:YAG Laser Photodisruption for Multilevel Premacular Hemorrhage due to Isolated Retinal Venous Macroaneurysm - Kenan Sonmez; Pehmen Y. Ozcan (Case Reports in Ophthalmological Medicine)
A 55-year-old man presented with sudden deterioration of vision in the right eye. His visual acuity was reduced to hand motion because of a large multilevel premacular hemorrhage. Nd:YAG laser was performed to drain the entrapped hemorrhage under the internal limiting membrane (ILM) and posterior hyaloid face in the macula into the vitreous. Immediately after laser treatment, streaming of red blood cells into the vitreous gel through the perforation site was observed. At the first-month follow-up, BCVA improved to 20/25 and ILM wrinkling was observed at the macula where the preretinal hemorrhage cleared. Fluorescein angiography revealed an isolated retinal venous macroaneurysm located on the macular branch of the superotemporal vein at the bifurcation site. In contrast to retinal arterial macroaneurysms, retinal venous macroaneurysms are quite rare. To the best of our knowledge, this is the first case reported with multilevel premacular hemorrhage caused by an isolated retinal venous macroaneurysm.